An improved strain-softening constitutive model of granite considering the effect of crack deformation - Yapeng Li; Qiang Zhang; Qiuxin Gu; Peinan Wu; Binsong Jiang (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
This paper presents an improved strain-softening constitutive model considering the effect of crack deformation based on the triaxial cyclic loading and unloading test results. The improved model assumes that total strain is a combination of plastic, elastic, and crack strains. The constitutive relationship between the crack strain and the stress was further derived. The evolutions of mechanical parameters, i.e. strength parameters, dilation angle, unloading elastic modulus, and deformation parameters of crack, with the plastic strain and confining pressure were studied. With the increase in plastic strain, the cohesion, friction angle, dilation angle, and crack Poisson's ratio initially increase and subsequently decrease, and the unloading elastic modulus and the crack elastic modulus nonlinearly decrease. The increasing confining pressure enhances the strength and unloading elastic modulus, and decreases the dilation angle and Poisson's ratio of the crack. The theoretical triaxial compressive stress-strain curves were compared with the experimental results, and they present a good agreement with each other. The improved constitutive model can well reflect the nonlinear mechanical behavior of granite.